The Representation of Consumptive and Productive Behaviours in English Textbooks for Senior High School Students - Manar, Marsandi; Feliza, Dinda Yasmin; Yastanti, Unpris; Wulan, Retno (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2025)
Abstract. This Hallidayan-based study aimed to investigate the representation of consumptive and productive behaviours in English textbooks for senior high school students. To obtain the purpose of this study, two grade-12 English textbooks used nationally in Indonesia were purposively selected. Then reading texts about finance issues were analysed by employing the Hallidayan SFL framework of material clause. Based on the analysis, it was found that the dominant material clauses (40%) in the books construe productive behaviours while the second frequent ones (32%) represent consumptive behaviours. However, there is the tendency to represent money as a goal. The findings of this study are expected to contribute to developing finance literacy in English textbook materials for Indonesian senior-high-school students. While the portrayal of productive behaviours in textbooks is salient for the development of their finance literacy, there is also a need to avoid building money-oriented paradigmKeywords: Productive, consumptive, behaviours, textbook, SFL